RATIO LEGIS RIGHTS MATERIAL TEST OF THE SUPREME COURT IN PERMA NUMBER 1 OF 2011 - Sonya Claudia Siwu (Awang Long Law Review, 2021)
Judicial power is the last bastion in upholding the rule of law. The Supreme Court as one of the holders of judicial power in Indonesia is expressly specified in Article 24 A Paragraph (1) of the 1945 NRI Constitution has the authority to test the laws and regulations under the law. The authority of the Supreme Court is further regulated in Article 20 paragraph (2) letter (b) of Law No. 48 of 2009 concerning the Power of Justice; and Article 31 A of Law No. 3 of 2009 on The Second Amendment of Law No. 14 of 1985 concerning the Supreme Court; and in Article 9 paragraph (2) of Law No. 12 of 2011 concerning the Establishment of Laws and Regulations (P3). Furthermore, to exercise its authority, the Supreme Court has enacted Supreme Court Regulation (PERMA) Number 1 of 2011 on Materil Test Rights. The Supreme Court's policy dictates that the trial is conducted behind closed doors with a limited time consideration of only 14 days while the case that goes to the Supreme Court is very much. In the development of the policy of carrying out the trial of material test rights behind closed doors drew criticism and rejection with arguments negating the sense of justice in the judicial environment. In this paper the authors try to look back at how PERMA Number 1 of 2011 was applied in a material test trial against the laws and regulations under the Act. The research method used in the discussion is to use the approach of norms, principles, theories, and concepts. In the end, the conclusion in this article is in order to realize justice, certainty and legal expediency and the independence and impartiality of judicial power in Indonesia as the last bastion of law enforcement, it is felt that changes are needed to PERMA No. 1 of 2011.